Concepções e práticas da convivência na atuação de terapeutas ocupacionais em Centros de Convivência e Cooperativas - Machado, Pietra Rosa Aguiar (Universidade Federal de São Carlos, 2026)
Social Interaction and Cooperative Centers (CECCOs) are strategic components of Brazil's mental health policy and the Psychosocial Care Network (RAPS), guided by principles of care within the community, social participation, inclusion, and the co-creation of the "common." These facilities feature interprofessional teams—notably including occupational therapists, whose practice has historically contributed to creating spaces for social interaction, participation, and cultural production, as well as strengthening community ties. Although social interaction holds a central place in the organization of these services and the practices of occupational therapists, the concept remains multifaceted and continues to evolve within the field of occupational therapy. Against this backdrop, the general objective of this research was to identify how occupational therapists at CECCOs in the city of São Paulo conceive and practice social interaction. A specific objective was to analyze the relationship between the conceptions of social interaction adopted by these professionals and the practices implemented in the services. This study employed a qualitative approach with an exploratory and descriptive design, conducted at eight CECCOs in São Paulo. Eight occupational therapists working at different CECCOs participated in the study; all had at least one year of experience in these services and were directly involved in daily social interaction practices. Data collection involved two instruments: an Occupational Therapist and CECCO Characterization Form and a semi-structured interview guide. Form data were analyzed descriptively, while interview data underwent thematic analysis. Four categories emerged from this analysis: Category 1 – Historical, organizational, and symbolic dimensions of CECCOs; Category 2 – Social interaction: conceptions, understandings, and practices; Category 3 – Interplay between social interaction and occupational therapy; Category 4 – Sociopolitical aspects of social interaction and their repercussions within CECCOs. The results show that social interaction emerges as a structuring axis of the work at CECCOs, revealing that interacting involves sharing experiences, building together, and recognizing the other in their uniqueness. They further highlight that this experience requires creating conditions where different ways of being and existing in the world are welcomed. This ethical dimension serves as a prerequisite for building more inclusive and solidary societies. Social interaction entails the continuous practice of recognizing the legitimacy of the other and sustaining relationships that transcend prejudices, stigmas, and normative expectations; this materializes in concrete practices regarding the organization of daily life, the facilitation of groups, the mediation of encounters, and the creation of spaces for participation and belonging. Thus, a close relationship is observed between how occupational therapists understand social interaction and the practices they implement; their conception of it as a relational, ethical, and collective process translates into interventions that prioritize encounters, listening, and openness to difference. Social interaction, as practiced in CECCOs, is considered a structuring axis of Occupational Therapy practice and a fundamental dimension of psychosocial care, contributing to the fostering of autonomy, social participation, and the right to the city, while highlighting the specific role of Occupational Therapy in sustaining practices committed to care within a context of freedom.
Conceptions and practices of social interaction in the work of occupational therapists in Social Interaction Centers and Cooperatives
Keywords: Terapia Ocupacional; Centro de Convivência; Atenção Psicossocial; Rede de Atenção Psicossocial; Convivência; Saúde Mental; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar